Analisis Potensi dan Strategi Pemasaran Destinasi Wisata Pantai The Legend Desa Padelegan Kabupaten Pamekasan - Wulan Safitri; Nurita Andriani (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to describe the potential and discuss the marketing strategy applied at The Legend Beach. This research was conducted at The Legend Beach, Padelegan Village, Pamekasan Regency. The types of data used in this study are primary data and secondary data collected through the process of observation, interviews, and documentation. The analytical tools used are SWOT analysis tools and 7P marketing mix which are then analyzed using Miles and Huberman model analysis techniques. Based on the SWOT analysis, there are several potentials that can be developed at The Legend Beach, including edutourism, mangrove ecotourism, cultural tourism, and the use of The Legend Beach as a promotional tool for the superior products of Padelegan Village. Marketing mix analysis resulted in marketing strategy recommendations, including equipping facilities at The Legend Beach, implementing 5S, providing souvenirs to tourists, setting new rates, improving road access to The Legend Beach, adding road signs, using promotional mix, improving quality and insight of Human Resources, clear division of teams and work, expanding parking areas, arranging uniforms for managers, increasing the number of pine trees around the beach.